THE SPIRITUAL AND PSYCHOLOGICAL VALUES IN â€œSEDEKAH BUMIâ€ OR THE EARTH ALMS TRADITION IN MURAHARJO VILLAGE, KUNDURAN SUB-DISTRICT, BLORA DISTRICT - Rochmawati, Nikmah; Choriroh, Uvik Zumrotul; Romadhoni, Tri Dewi; Magiman, Mohamad Maulana (Universitas Mercu Buana Yogyakarta, 2021)
â€œSedekah Bumiâ€ or the Earth alms in Muraharjo village is a traditional ritual conducted as a form of thanksgiving to God for the bountiful harvest. This study aims to determine Islamic spiritual value and the psychological value of the inhabitants of Muraharjo village on the earth alms tradition. The approach used in this research is a qualitative approach with ethnographic methods. The sampling technique used was purposive sampling. Participants in this study consisted of 4 people with the criteria of residents of Muraharjo village, Kunduran, Blora who have lived in the village for more than ten years, aged 20 years and over, participated in organizing earth alms, and understood the origins of the village's earth alms. The data collection technique was done by interview and observation. The data analysis technique used descriptive analytic technique namely data reduction, data presentation, and conclusion making. This study indicates that the tradition of earth alms giving in the village of Muraharjo, Kunduran, Blora is still implemented every year. According to the participants' understanding of Islam, the earth alms tradition does not violate Islamic law, nor is it an act of shirk (syirik).Â People cognitively believe that carrying out the ritual of Earth alms will bring safety, fertility, and abundant future harvests from a psychological perspective. From a practical point of view, people feel calm, happy, and safe so that behaviorally, people still carry out and preserve earth alms activities up to this present.Â